2010
DOI: 10.1017/s0031182010001162
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity ofBabesiainIxodes persulcatusand small mammals from North Ural and West Siberia, Russia

Abstract: To our knowledge, this is the first detection of Babesia sensu stricto in I. persulcatus ticks and of B. microti in I. persulcatus in the Asian part of Russia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 32 publications
3
31
0
2
Order By: Relevance
“…However, unlike I. persulcatus, in which PCR detected the B. microti U.S. lineage, all sympatric I. ovatus ticks tested were negative. This specific I. persulcatus-U.S. lineage relationship was observed in previous studies in Japan (33) and Russia (31). In the Novosibirsk region in Russia, where the B. microti U.S. lineage is distributed in voles, mice, and shrews, I. persulcatus ticks are found to carry U.S. lineages.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, unlike I. persulcatus, in which PCR detected the B. microti U.S. lineage, all sympatric I. ovatus ticks tested were negative. This specific I. persulcatus-U.S. lineage relationship was observed in previous studies in Japan (33) and Russia (31). In the Novosibirsk region in Russia, where the B. microti U.S. lineage is distributed in voles, mice, and shrews, I. persulcatus ticks are found to carry U.S. lineages.…”
Section: Discussionsupporting
confidence: 84%
“…In the Eurasian region where I. scapularis is absent, PCR surveillance and DNA sequence analyses of field-collected ticks have revealed that Ixodes persulcatus (31)(32)(33) and Ixodes ricinus (1,34,35) in Asia and Europe, respectively, carry the B. microti U.S. lineage. Although experimental transmission of B. microti U.S. lineage to hamsters or gerbils has been shown (33,36), there is still a lack of biological evidence demonstrating the live pathogen in field-derived specimens.…”
mentioning
confidence: 99%
“…(rodents), and Sorex spp. (shrew) in Eurasia, including Japan (2,4,9,21,37,38). The two regional taxa of the Hobetsu and Munich, biologically inseparable from U.S. parasites but distinctive phylogenetically by the ␤-tubulin and CCT7 gene analyses, are common in Japan and Europe, respectively.…”
mentioning
confidence: 99%
“…Babesia DNA was detected by nested PCR based on the 18S ribosomal RNA (rRNA) gene as previously described (Rar et al 2011). Primary reactions were carried out using the forward primer BS1 (5′-gacggtagggtattggcct-3′) and reverse primer BS2 (5′-attcaccggatcactcgatc-3′).…”
Section: Dna Extraction Pcr and Sequencingmentioning
confidence: 99%
“…B. microti 'US' type was detected in I. persulcatus ticks, small rodents, and shrews from I. persulcatus distributive area in Siberia and the Far East (Zamoto et al 2004;Rar et al 2010Rar et al , 2011Rar et al , 2014a. In contrast, small mammals from I. persulcatus/ Ixodes trianguliceps sympatric areas located in Ural and West Siberia were shown to be infected with B. microti 'Munich' type or with both B. microti 'US' type and 'Munich' type (Rar et al 2011(Rar et al , 2014bNefedova et al 2012).…”
Section: Introductionmentioning
confidence: 99%